Integrating the Arts in Socially Accountable Health Professional Education With a Case Study at James Cook University - Sameshima, Pauline; Woolley, Torres; Preston, Robyn; Cameron, Erin; Cheu, Hoi F.; Allison, Jill; Clithero-Eridon, Amy (Art/Research International)

(untitled) (University of Alberta, 2026)
This research examines how Socially Accountable Health Professional Education (SAHPE) fosters transformative learning and professional identity formation, focusing on the multi-site Stories and Art of Local Transformation in Health Education project. SAHPE aligns education, research, and service with the needs of underserved communities. Using arts integrated methods and the parallaxic praxis framework, the project engaged students and faculty in creative workshops and reflective dialogue about social accountability. Case study findings from James Cook University show that a socially accountable curriculum—enhanced by diverse recruitment, rural placements, and faculty role modelling—supports equity-oriented values and advocacy skills. The arts enabled participants to express complex experiences, deepening compassion, and critical reflection. Explicit arts integrated SAHPE approaches may prepare future health professionals to address health disparities and promote universal health care.